Whether $(a-k)^p-(a-h)^p\ge (h-k)^p$ for all $a>h>k>0 , ~p\ge1$ ?

I try some simple value, for example $a=3,h=2,k=1, p=2$ and so on. This inequality is right, but how to prove it ?


I think it's true.

$$(a-k)^p=(a-h+h-k)^p>(a-h)^p+(h-k)^p.$$ Indeed, let $a-h=x$ and $h-k=y$.

Thus, we need to prove that $$(x+y)^p>x^p+y^p.$$ Since the last inequality is symmetric of $x$ and $y$, we can assume that $x\geq y$.

Now, since $f(x)=x^p$ is a convex function and $(x+y,0)\succ(x,y)$, by Karamata we obtain: $$(x+y)^p+0^p>x^p+y^p$$ and we are done!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.